(untitled) (Tempo e Argumento, 2021)
The article foregrounds Father Paulo Ricardo’s activity role in the political history of the present time. By building actions of political-religious guidelines that helped the shaping and mobilization of Jair Bolsonaro’s extreme right wing project, from 2018’s candidacy to the presidency. From this period, the management of the Covid-19 pandemic stands out. From the notion of Christofascism, as a “theology of authoritarian power”, one seeks to understand how the referred priest helps in intellectual production, hence sustaining the governmental summit mainly with the arrival of Covid-19 in the country. Also, the article seeks the notion of “trajectory” by Giovanni Levi to trace the last years of the priest’s religious activity, mainly from his productions on social media of political-religious appeal, when he directly feeds what we call Bolsonaro’s “Christofascism” with themes that help in the“ war of the gods ”promoted in this condition, in contempt for science and helping to feed this new type of authoritarianism experienced in contemporary Brazil. Keywords: Father Paulo Ricardo; political history; digital history; Christofascism.